Spiritual Emotional Freedom Technique for Anxiety in Asthma Patients: Implementation as A Non-Pharmacological Intervention in the Emergency Department - Fara Nabila; Beti Kristinawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Asthma is a chronic health problem that significantly impacts physical and psychological conditions, especially during emergencies in the emergency department (ER). Anxiety in asthma patients can worsen clinical conditions and prolong recovery time if not promptly addressed. This study aims to assess the effectiveness of Spiritual Emotional Freedom Technique (SEFT) as a non-pharmacological technique to reduce anxiety in asthma patients in the emergency department of Soeradji Tirtonegoro Regional Hospital, Klaten. This study was conducted descriptively through a case study of one asthma patient with anxiety disorders, using the Hamilton Anxiety Rating Scale (HARS) instrument before and after the SEFT intervention. The SEFT implementation was structured for 15 minutes, which included the stages of setup techniques, tune-in, and tapping on the body's energy points. The results of the measurements and assessments were analyzed using a nursing care approach. The measurement results showed a decrease in the patient's anxiety score from 17 (moderate) to 14 (mild) after SEFT, accompanied by clinical improvements such as respiratory rate stability and increased psychological comfort. Family support during therapy plays an important role in accelerating the reduction of anxiety and patient recovery. Based on the results and discussion, it can be concluded that SEFT is effective as a psychological intervention to reduce anxiety in asthma patients in emergencies, and can be integrated with breathing education and oxygen saturation monitoring for optimal results.